2021
DOI: 10.24191/ji.v16i1.373
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Credit Risk: Evidence From Commercial Banks in Malaysia

Abstract: The purpose of this study is to determine the relationship between microeconomic factors with credit risk among selected commercial banks in Malaysia. For this purpose, a sample of seven out of 27 commercial banks in Malaysia was selected and the microeconomic factors affecting credit risk with six measurements of return on asset (ROA), bank size, leverage, the ratio of capital, interest income and return on equity (ROE) were examined by applying Panel Regression Fixed Effect (FE) Model for a period 20 years f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…As a result, the banks may have held a more significant proportion of their capital in financial reserves, less credit. Moreover, Iqbal, Shafiq, Singh, and Afzal (2023);Muhamad Yusuf et al (2021); Rahman and Shahimi (2010); Sufian (2009) found that larger traditional banks have the potential to diversify their asset portfolio efficiently and; therefore, lower credit risks. Moussa (2015) found that liquidity is an essential variable for the bank and the managing an account framework parts.…”
Section: Liquidity With Credit Riskmentioning
confidence: 99%
“…As a result, the banks may have held a more significant proportion of their capital in financial reserves, less credit. Moreover, Iqbal, Shafiq, Singh, and Afzal (2023);Muhamad Yusuf et al (2021); Rahman and Shahimi (2010); Sufian (2009) found that larger traditional banks have the potential to diversify their asset portfolio efficiently and; therefore, lower credit risks. Moussa (2015) found that liquidity is an essential variable for the bank and the managing an account framework parts.…”
Section: Liquidity With Credit Riskmentioning
confidence: 99%